Growth and sporulation of Verticillium lecanii isolates under different environmental conditions - Monteiro, Antonio Carlos; Barbosa, Claudio Camargo; Correia, Antônia do Carmo Barcelos; Pereira, Gener Tadeu (Pesquisa Agropecuaria Brasileira, 2004)
This research aimed to evaluate the growth and sporulation of two Verticillium lecanii (Zimm.) Viégas isolates cultivated on solid medium with different initial pH values (4, 5, 6, 7, 8 and 9), exposed to different temperatures (19, 22, 25, 28 and 31°C) and photoperiods (0, 12 and 24 hours). There was no substantial effect of the initial pH values on growth and sporulation of both isolates twenty days after inoculation, except at pH 4.0 in which the growth was significantly reduced. Absence of light promoted the best growth of JAB 02 (32.70 mm) and JAB 45 (32.67 mm) isolates but there was no effect of photoperiod on sporulation. The best temperatures for growth of JAB 02 were 19, 22 and 25°C and for JAB 45, 19 and 25°C. The latter isolate sporulated most at 19 and 22°C and there was no effect of temperature on sporulation of JAB 02. None of the isolates developed at 31°C.